REGRESI LINEAR DALAM PENENTUAN NILAI GUNA LANGSUNG KAWASAN SINDANG GILA PROPINSI NTB DENGAN METODA TCM - Dewi Laraswati; Didik Purnomo (Universitas Bina Sarana Informatika, 2014)
This study uses the travel cost method (TCM), the processing of data using SPSS. The purpose of this study was to determine the estimated economic value of the region Sindang Mad as tourist services provider with a variable frequency of visits, total cost, age, education, income, length of visit and alternate locations. From the analysis of the data it can be seen that crazy Sindang tourist areas provide economic value based on its function as a tour provider of Rp.56,326,766,200 per hectare with a total benefit based on its function as a provider of travel services at Rp. 112 653 532400.Keyword: Value To Direct Regions, Travel Cost Method, SPSS, frequency of visits, total cost, age, education, income, length of visit and alternate locations